Morfometriks dan Meristik Lobster Air Tawar (Cherax quadricarinatus) pada Perairan Rawa Aopa Konawe Selatan - Andi Irwan Nur; Vivi Satia Yanti Engko; Yustika Intan Permatahati (Jurnal Manajemen Sumber Daya Perairan, 2023)
This study aims to determine the morphometrics and meristics of freshwater crayfish in Rawa Aopa Waters, Puwuta Village, Angata District, South Konawe Regency. The research were carried out using a purposive sampling method based on habitat characteristics. Station I is located 200 m from the residential area with an average current speed of 0.07 m/s. Station II is located 800 m from the residential area with an average current speed of 0.10 m/s. Station III 1.3 km from the residential area with an average current speed of 0.12 m/s. Sampling was carried out by simple random method for two months using modified traps from used gallons of water. Morphometric data analysis was performed using Analysis One Way Anova (ANOVA) and meristic component analysis was analyzed descriptively. The number of lobsters caught during the study amounted to 104 with 56 males and 48 females. The size distribution of the male and female lobsters caught were juveniles with a range of 2.86-9.90 cm and 4.41-9.86 cm to adults with a range of 10.38-13.48 cm and 10.55-15.71 cm respectively. The morphometric characteristics measured included the length of the carapace at the front, the length of the carapace at the back, the length of the stomach and the length of the tail (telson). The meristic characteristics that are counted include the number of spines on the telson, dactylus and propodus.